2019
DOI: 10.1111/roiw.12407
|View full text |Cite
|
Sign up to set email alerts
|

Eliciting, Applying And Exploring Multidimensional Welfare Weights: Evidence From The Field

Abstract: By combining primary data on dimension importance collected in the field from three different samples and nationally representative survey data from the Dominican Republic, we offer a twofold contribution. The first one comes from an unincentivized questionnaire experiment, where the significance of the treatment effect shows that life domains are valued differently in a poverty vs a well-being framework. This poses important questions on the anatomy of dimension importance and on the use of weights in empiric… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
9
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 9 publications
(9 citation statements)
references
References 90 publications
0
9
0
Order By: Relevance
“…Our survey also included a module to capture the importance people assign to each of the 12 dimensions of wellbeing included in the survey. This module followed an ordinal scale valuation approach (Esposito & Chiappero‐Martinetti, 2019 ). Specifically, the enumerators asked respondents to indicate how important each dimension was to them by way of a 12-step ladder scale, whose first step indicated that a dimension was “not important at all” and whose 12th step corresponded to an “absolutely important” dimension (see Fig.…”
Section: Datasetmentioning
confidence: 99%
See 1 more Smart Citation
“…Our survey also included a module to capture the importance people assign to each of the 12 dimensions of wellbeing included in the survey. This module followed an ordinal scale valuation approach (Esposito & Chiappero‐Martinetti, 2019 ). Specifically, the enumerators asked respondents to indicate how important each dimension was to them by way of a 12-step ladder scale, whose first step indicated that a dimension was “not important at all” and whose 12th step corresponded to an “absolutely important” dimension (see Fig.…”
Section: Datasetmentioning
confidence: 99%
“…In turn, Greco ( 2018 ) developed a capability-based multidimensional wellbeing measure for women in a rural district of Malawi (Women’s Capability Index for Malawi) using different weighting schemes: data-driven (based on principal component analysis), normative (based on focus-group consensuses on the values of the dimensions), hybrid (based on individual-level survey information on dimensional importance rankings), and equal weights. Another significant recent contribution to this field is the study by Esposito and Chiappero‐Martinetti ( 2019 ), who used the budget allocation technique to set weights based on information from a non-statistically representative sample administered in the Dominican Republic.…”
Section: Design Of the Mwi-pmentioning
confidence: 99%
“…A meaningful review of the issues related to the weighting structure is proposed by [11], who stress both the relevance and the subtleness of this topic.…”
Section: The Weighting Structurementioning
confidence: 99%
“…There seems to be some empirical evidence that ‘individual’ opinions on what dimensional weights are appropriate do depend on the existing state of affairs. See, for instance, Esposito and Chiappero-Martinetti (2013). It seems reasonable to deduce that if the ‘society’s’ opinion is not entirely independent of the opinions of its constituent units, a similar remark would apply to ‘social’ value judgements regarding the weights.…”
Section: Introductionmentioning
confidence: 99%